Physicochemical Characteristics of Carrageenan Based on Different Harvesting Times From Bontang Coastal, East Kalimantan - Andi Noor Asikin; Indrati Kusumaningrum (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Proper harvesting time determines the physicochemical characteristics of carrageenan. The purpose of this study was to determine the physicochemical characteristics of carrageenan extracted from Kappaphycus alvarezii at various different harvesting times from the Bontang Coastal, East Kalimantan. This study consisted of 7 treatments at the harvesting times, which were harvested at 30; 35; 40; 45; 50; 55 and 60 days. The parameters observed included yield, moisture content, ash content, viscosity and gel strength. The results showed the highest yield at the age of 50 days of harvest (46.91%), the highest viscosity at the age of55 days harvest (50.25 cP), and the highest gel strength at 40 days of harvesting at 60.14 g/cm2.